2007
DOI: 10.1099/vir.0.83146-0
|View full text |Cite
|
Sign up to set email alerts
|

A short treatment of cells with the lanthanide ions La3+, Ce3+, Pr3+ or Nd3+ changes the cellular chemistry into a state in which RNA replication of flaviviruses is specifically blocked without interference with host-cell multiplication

Abstract: Alpha- and flaviviruses contain class II fusion proteins, which form ion-permeable pores in the target membrane during virus entry. The pores generated during entry of the alphavirus Semliki Forest virus have been shown previously to be blocked by lanthanide ions. Here, analyses of the influence of rare earth ions on the entry of the flaviviruses West Nile virus and Uganda S virus revealed an unexpected effect of lanthanide ions. The results showed that a 30 s treatment of cells with an appropriate lanthanide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Wengler et al also demonstrated that lanthanide ion (such as La(III) and Ce(III)) treatment blocks the ability of the host cell to support the replication of flavivirus (envelope type virus) RNA. A similar effect of La(III) is expected to contribute to the inactivation of Qβ [ 45 ]. The slight antiviral activity shown by CeO 2 might be attributable to the major Ce ion valence (not III but IV).…”
Section: Resultsmentioning
confidence: 99%
“…Wengler et al also demonstrated that lanthanide ion (such as La(III) and Ce(III)) treatment blocks the ability of the host cell to support the replication of flavivirus (envelope type virus) RNA. A similar effect of La(III) is expected to contribute to the inactivation of Qβ [ 45 ]. The slight antiviral activity shown by CeO 2 might be attributable to the major Ce ion valence (not III but IV).…”
Section: Resultsmentioning
confidence: 99%
“…This photo‐shrinkage of the sacran gels may be attributed to the hydrophobization of uronic acid based on photo‐decarboxylation. These phenomena could be seen in other trivalent ions whose controlled release might be effective in cancer targeting (if radioactive ions were used) and virus infection control . Furthermore, any polysaccharides containing hexose can be materialized using the present photoreaction‐mediated phenomenon because uronic acid can be easily converted from hexose by oxidation.…”
Section: Metal Adsorptionmentioning
confidence: 97%
“…This photoshrinking is expected to occur in a mixture with other trivalent ions. It is expected that, by using the composites, controlled release will be useful in targeted cancer therapies [47] and virus infection controls [48].…”
Section: Lc Gel Formationmentioning
confidence: 99%